(untitled) (Lundiana: International Journal of Biodiversity, 2016)
Factors such as the discordance on the choice of characters by different authors and the fragmentary condition of the majority of fossils are responsible for many issues on the taxonomy of the South American Tayassuidae. The extinct Tayassuidae species Catagonus stenocephalus (Lund in Reinhardt 1880) presents a confuse nomenclatural history and a questionable genus designation. The morphometric analysis performed in this study, based on craniomandibular and dental characters, allowed to distinguished three groups morphologically distant from each other within the Catagonus genus. This result highlights the need for more precise phylogenetic analysis for the definition of taxonomic groups in the South American Tayassuidae.